Communication, inclusion, and environmental justice - journalists’ attitudes towards low-carbon city transformation in China - Wu, Yan; Martens, Pim; Krafft, Thomas (Frontiers in Environmental Science, 2025)
Cities are recognized as significant contributors to carbon emissions due to their numerous productive enterprises and dense populations. Tackling climate change and achieving the transformation to low-carbon cities requires public participation. News media serve as the primary channel for the public to gain relevant information, and journalists’ attitudes significantly influence the content of related news reports. This study focuses on the attitudes of Chinese journalists towards the transition to low-carbon cities, using semi-structured interviews in qualitative research to conduct 31 interviews with participants from Chinese mainstream medias. This research discussed the journalists’ attitudes towards the low-carbon city transition, based on our samples studies, we find that (1) low-carbon city development brings some new opportunities for economic development and improving the overall urban living environment, despite challenges like lack of professional knowledge and information gaps. (2) Newsworthiness, audience preferences, journalists’ climate scientific knowledge, and management mechanisms, are key factors influencing journalists’ choice to cover low-carbon topics. Despite an increase in related reports, many media do not prioritize climate change or low-carbon transitions as core topics, and environmental news have a life cycle. (3) We suggests that media enhance collaboration with stakeholders, increase audience interaction to learn diverse voices, using storytelling and integrating technological innovations to improve low-carbon communication. This study highlights the complex interactions between media, public participation, and environmental policies, offering a holistic view of the challenges and opportunities in promoting more inclusive and equitable low-carbon city transition.